Effects of Pharmacist-Led Clinical Pathway/Order Sets on Cancer Patients: A Systematic Review - Tan, Zhiyuan; Yu, Zhiheng; Chen, Ken; Liu, Wei; Zhao, Rongsheng (Frontiers in Pharmacology, 2021)
Background: Pharmacists-led clinical pathways/order sets (PLCOs) were first applied for designated diseases and surgical operations, such as cancer. They were not used in pharmacotherapy until recently. After screening a large number of publications, we found that PLCOs were rarely accessible. Objective: To evaluate the effects and the changes of relevant medical outcomes of PLCOs. Methods: Articles from Pubmed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database and China Biology Medicine disc (CBM) were systematically retrieved. Clinical research comparing cancer patients’ clinical effects with or without clinical pathway/order sets were identified. Two reviewers performed quality assessment and the data was abstracted independently. A narrative synthesis of the extracted data was performed due to heterogeneity. Results: Nine studies were identified; including 6 uncontrolled before-after studies and 3 case-series studies respectively. The scopes of PLCOs of included research can be divided into 2 types; one focusing on chemotherapy agents, the others on the managements of chemotherapy-induced complications. The PLCOs shortened hospital length of stay, decreased initial antibiotic time intervals in patients with febrile neutropenia, reduced medication error incidence and increased physicians’ adherence rate to clinical pathway/order sets. Moreover, 3 articles included economic effects showing positive savings on medication costs through PLCOs. Conclusions: PLCOs can have beneficial effects on medication effectiveness, safety, and economic outcomes. Nevertheless, clinical pathway/order sets need to be further optimized and expanded to other clinical areas.